136. Factors Associated with Reduced Vancomycin Susceptibility in Pediatric Staphylococcus aureus Bacteremia - Ericson, Jessica E (Open Forum Infect Dis, 2019)
BACKGROUND: Vancomycin is often used empirically for treatment of pediatric Staphylococcus aureus bacteremia while susceptibility testing is being performed. Reduced vancomycin susceptibility (RVS) occurs when the minimum inhibitory concentration (MIC) for vancomycin is elevated, potentially resulting in decreased efficacy. Patient factors associated with RVS in pediatric S. aureus infections have not been well studied. METHODS: Children aged <18 years admitted from 2012 to 2016 to two tertiary care children’s hospitals with a blood culture positive for S. aureus were identified. Demographics, presence of comorbidities, hospitalizations in the year prior to the infection, surgical procedures in the 30 days prior to the infection, presence of a central venous catheter at diagnosis and methicillin-resistant (MRSA) vs. methicillin-susceptible S. aureus (MSSA) were abstracted from the electronic medical record using a structured data collection form. RVS was defined as a MIC >1 µg/mL as reported by the clinical microbiology laboratory. Wilcoxon rank-sum and Fisher’s exact test to compare continuous and categorical variables, respectively. A multivariable logistic regression model was used to evaluate the association of RVS with patient factors, MRSA vs. MSSA, admitting hospital, and year. RESULTS: We identified 221 S. aureus bloodstream infections. Most (84%) had RVS though there were differences by the hospital, 74% vs. 87%, P = 0.037. Bloodstream infections in the setting of a musculoskeletal infection were most common (36%), followed by central line-associated bloodstream infections (22%). The median age was similar between RVS and non-RVS infections, 3 (25(th), 75(th) %tiles: 0, 9) vs. 5 (0, 12) but, when adjusted for patient factors, younger children were more likely to have RVS infections than older children, aOR: 0.92 (0.85, 0.99). Black children were more likely to have RVS than white children on both univariate and adjusted analyses (table). CONCLUSION: RVS is common among pediatric S. aureus bloodstream infections and appears to be influenced by patient age and race but not by the source of the infection or other clinical factors. [Image: see text] DISCLOSURES: All authors: No reported disclosures.